2012
DOI: 10.4161/psb.19940
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reactive oxygen species generation under drought conditions in Arabidopsis

Abstract: Responses to adverse environmental conditions are regulated by gene regulatory networks, in which transcription factors play a central role in plants. The NAC transcription factors constitute a representative transcription factor family that mediate diverse aspects of biotic and abiotic stress responses in plants. 1 Notably, some NAC transcription factors are integrated into the intracellular membranes and proteolytically activated upon exposure to developmental and external stimuli.2,3 At least 13 membranebou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…These experiments were repeated three times with similar results. Examination of the other TMD-containing NACs showed that NAC053/NTL4 positively regulates H 2 O 2 -dependent drought stress responses and NAC017 negatively regulates these responses (Lee and Park, 2012;De Clercq et al, 2013 (Olsen et al, 2005). NAC017 also binds to the core sequence of the NAC binding motif, CACG or CAAG (Ng et al, 2013).…”
Section: Nac016 Binds To a Unique Motif That Differs From The Core Namentioning
confidence: 99%
See 3 more Smart Citations
“…These experiments were repeated three times with similar results. Examination of the other TMD-containing NACs showed that NAC053/NTL4 positively regulates H 2 O 2 -dependent drought stress responses and NAC017 negatively regulates these responses (Lee and Park, 2012;De Clercq et al, 2013 (Olsen et al, 2005). NAC017 also binds to the core sequence of the NAC binding motif, CACG or CAAG (Ng et al, 2013).…”
Section: Nac016 Binds To a Unique Motif That Differs From The Core Namentioning
confidence: 99%
“…Conditional Nuclear Localization of NAC016 by Cleavage of the C-terminal TMD under Drought Stress or Prolonged Darkness NAC016 contains a C-terminal TMD , and the C-terminal TMD determines the subcellular localization of other NACs (Lee and Park, 2012;De Clercq et al, 2013;Ng et al, 2013). Thus, to examine whether the C-terminal TMD of NAC016 controls its conditional nuclear localization, we prepared transgenic plants expressing the full-length NAC016 (N16) or NAC016 without the TMD (N16△C).…”
Section: Arabidopsis Nac016 Mutants Tolerate Drought Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of them possess stress responsive cis-regulatory elements in their promoter sequences like abscisic acid-responsive elements (ABRE) and drought-responsive elements (DRE) [189][190][191]. The plasma membrane-associated NTL4 (NAC transcription factor) after drought or ABA treatment has been shown to be proteolytically activated and transported to the nucleus where it induces expression of NADPH oxidase involved in ROS generation [192]. Moreover, the dehydration stimulates expression of BAX inhibitor-1 (AtBI-1).…”
Section: Drought Stress -Soil Water Deficitmentioning
confidence: 99%